Genetic and Bacteriological Study of Aerobic Bacteria Which Causes Cesarean Section Contamination in Women in The City of Diwaniya - Alkaby, W. a. A. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was designed  to stand  on the most important causes of contamination in sesarean section in women by the aerobic bacteria species the bacteria isolates  were diagnosed in the Maternity and Children  Hospital in the Qadsiya province and in the special clinics. Sixty five persent of women having cesarean operation were contaminated with different bacteria in different ratios. Staphylococcus aureus  showed the higher percentage  (62.4) , Pseudomonas.aerogenosa  18% , E.coli 9.5% and Proteus.spp (6,4%).While Streptococcus pyogens showed lowest percentage 3.6% .  The results of antibiotic sensitivity test for all bacteria  isolates showed  Chloramphenicol and Amikacin where efficient in it effect on bacteria , while Amoxicillin and Ampcillin where low efficient in there effect .  About antibiotic combination test on  Staphylococcus aureus and Pseudomonas aerogenosa the results showed syneergstic effect between Amoxicillin and Gentamycin  and cefotaxin. The results of electophoresis of DNA that extracted from species of isolated bacteria, showed that E.coli Pseudomonas.aerogenosa and Proteus spp one plasmid band while Staphylococcus contain two small plasmid band and there is no relation ship between the number of bands and the resistance for antibiotics.